INFLUENCE OF WORK DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT XYZ KUNINGAN MSMEs, WEST JAVA - Gessa Mertha Asri; Dene Herwanto (Universitas Mercu Buana, 2021)
Human Resources (HR) is something that is very important in a company because it can affect whether or not a company is good. Small, Micro and Medium Enterprises (MSMEs) XYZ is a business unit engaged in the food sector, namely making tofu such as skin tofu, milk tofu, wet tofu, etc. This study aims to determine whether there is an influence between work motivation and work discipline on employee performance. The research method used is descriptive quantitative, namely discussing the company's problems with work discipline and work motivation on employee performance. This research was conducted by distributing questionnaires to 15 employees at MSMEs XYZ. Based on the research that has been done, from the results of the partial test (t test) that the Work Motivation variable (X2) has an effect on Employee Performance (Y) with a significant value of 0.048 <0.05 because the significant value of t count is smaller than t table.